Experimental and modeling study of burning velocities for alkyl aromatic components relevant to diesel fuels - Mehl, Marco; Herbinet, Olivier; Dirrenberger, Patricia; Bounaceur, Roda; Glaude, Pierre-Alexandre; Battin-Leclerc, Frédérique; Pitz, William J. (Proceedings of the Combustion Institute, 2015)
Aromatic species represent a significant fraction (about one third by weight) of both diesel and gasoline fuels. Much of the aromatics in diesel and gasoline are alkyl-benzene species. Although toluene, the lightest of the alkyl-benzenes, has been the subject of extensive literature investigations, very little experimental data are available for heavier alkyl-benzenes (9–20 carbon atoms) relevant to diesel fuel. In this work, the burning velocity of ethyl-, n-propyl- and n-butyl-benzenes were measured in a premixed flat-flame burner using the heat flux method. The burning velocities were measured as a function of the equivalence ratio at atmospheric pressure and for two unburned gas temperatures (358 and 398K). These new experiments are compared with burning velocities for toluene previously measured by the authors. The comparisons showed that ethyl-benzene has the highest flame speed, followed by n-propyl- and n-butyl-benzenes which have similar burning velocities. Toluene has the lowest flame speed. Excellent agreement was observed between the new measurements and simulations using a mechanism for alkyl-benzenes recently published by Lawrence Livermore National Laboratory (LLNL) and National University of Ireland. Based on the strong correlation between experiments and calculations, different aspects contributing to the burning speed of the fuels (thermal effects, kinetics, …) were analyzed using the model. A sensitivity analysis was used to determine the reaction rate constants that are most important in determining the flame speed. Reaction path analysis and species profiles in the flame were used to identify the key reaction paths that lead to increase or decrease in the burning velocities. Contrary to what is generally observed for alkanes whose flame speed is controlled by small radical fragments, the flame speed of aromatics is influenced by fuel specific intermediates such as phenyl, benzyl, or even heavier species. The new experimental data and modeling insight generated by this work will support the development of models for heavier alkyl-aromatics of great relevance to diesel fuel.